COMMUNITY SERVICE OF DR. KOFFIE BANDAR LAMPUNG ON DIGITAL MARKETING TRANSFORMATION - Rahman , Fathur; Khamidah, Yuyun; Wulansari , Dita; W.P, M. Firas; Istyqomah, Ajeng; Fitria, Suci; Roslina, Roslina (CV. Tripe Konsultan, 2023)
Small and medium-sized enterprises (SMEs) is a businesses whose personnel and revenue numbers fall below certain limits. The abbreviation